Do fewer people mean fewer cars? Population decline and car ownership in Germany - Nolan Ritter; Colin Vance (Transportation Research Part A: Policy and Practice, 2013)
Drawing on household data from Germany, this study econometrically analyzes the determinants of automobile ownership, focusing specifically on the extent to which decreases in family size translate into changes in the number of cars at the national level. Beyond modeling several variables over which policy makers have direct leverage, including the proximity of public transit, fuel prices and land use density, the analysis uses the estimated coefficients from a multinomial logit model to simulate car ownership rates under alternative scenarios pertaining to demographic change and other socio-economic variables. Our baseline scenario predicts continued increases in the number of cars despite decreases in population, a trend that is attributed to continued increases in household income.
Keywords: 330; Car ownership; Demographic change; Germany; Multinomial logit; Simulation